Proceedings of the 14th International Conference on Intelligent User Interfaces 2009
DOI: 10.1145/1502650.1502686
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the intent behind mobile information needs

Abstract: Mobile phones are becoming increasingly popular as a means of information access while on-the-go. Mobile users are likely to be interested in locating different types of content. However, the mobile space presents a number of key challenges, many of which go beyond issues with device characteristics such as screen-size and input capabilities. In particular, changing contexts such as location, time, activity and social interactions are likely to impact on the types of information needs that arise. In order to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
154
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(168 citation statements)
references
References 19 publications
11
154
0
1
Order By: Relevance
“…These results are in accordance with the findings by Church and Smyth [33], who used diary studies to show that ''many users have a variety of information needs when they are away from their familiar contexts''. However, our work goes further by providing a quantitative way to characterise the familiarity of these contexts.…”
Section: Exploring Departures From Routine In the Nokia Datasetsupporting
confidence: 91%
“…These results are in accordance with the findings by Church and Smyth [33], who used diary studies to show that ''many users have a variety of information needs when they are away from their familiar contexts''. However, our work goes further by providing a quantitative way to characterise the familiarity of these contexts.…”
Section: Exploring Departures From Routine In the Nokia Datasetsupporting
confidence: 91%
“…Mobile users tend to locate different types of content while on the go ( Google, 2016a ). Local services, points of interest (POIs) and driving directions are some of the most popular mobile information needs of the users ( Church and Smyth, 2009;Sohn et al, 2008;Teevan et al, 2011;Kamvar and Baluja, 2006;Google, 2016a ). Location information on the mobile devices has enabled people to use mobile local search services as 30% of all mobile searches are reported to be related to location ( Google, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of "just-in-time" information behaviors, 27% and 41% of those sampled indicated they used their mobile phones to settle an argument or coordinate a social gathering, respectively, within the past month (Rainie & Fox, 2012). Further, mobile search is often conducted in the presence of others (Church & Oliver, 2011;Amin, Setlur, Xi, Hayashi & Hong, 2009;Teevan, Karlson, Amini, Brush & Krumm, 2011), and searches may be socially motivated (Rahmati & Zhong, 2012) or prompted by conversations (Church & Smyth, 2009;Sohn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%